The Relationship Between Criminal Policy And Social Policy - Askamaini Askamaini; Yasmirah Mandasari Saragih; Sumarno Sumarno; Wildan Fahriza; Darma Setiawan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Crime or criminal acts, apart from being a humanitarian problem, are also social problems, they are even stated to be the oldest social problem . When carrying out crime prevention efforts, it must be seen in the context of overall social policy, the aim of which is to provide community protection and achieve community welfare. The aim of this research is to find out and analyze the relationship between criminal policy and social policy. This research was conducted descriptively analytically. Criminal policy is one of the fields of modern criminal law ( modern criminal sciences ) which consists of several components, namely criminology, criminal law, science and at the same time art . . Criminal policy as an effort to overcome crime has the main objective of protecting and creating community welfare. Achieving a level of social welfare and social protection is a national goal in implementing social policy .